Streptococcal Pharyngitis and Appendicitis in Children. (January 2018) - Nielsen, Jason W.; Abel, Stuart A.; Kenney, Brian
Background . Several pathologies, including pharyngitis, are associated with abdominal pain that can mimic appendicitis. We sought to further understand the link between appendicitis-like symptoms and streptococcal (strep) pharyngitis. Methods . All patients undergoing ultrasound imaging for appendicitis in our emergency department during 2013 were reviewed (n = 1572). A total of 207 patients were identified who underwent both ultrasound for appendicitis and testing for strep pharyngitis. Demographic and outcomes data between rule out appendicitis patients who underwent strep testing and those who did not were compared. Results . Strep testing was more common in younger patients (mean age = 8.26 vs 10.26 years P < .001) and evenly matched by gender (104 male, 103 female). Of the 207 patients tested for strep pharyngitis, 8 (3.9%) patients had appendicitis and 35 (16.9%) patients tested positive for strep pharyngitis. No cases of concurrent strep pharyngitis and appendicitis were identified. The negative appendectomy rate in the strep pharyngitis tested group was 38.5% (5/13), compared with 7.7% (23/296) ( P = .003) in the nontested group. The appendicitis rate among the strep tested group was 3.8% (8/207) compared with 20% (273/1365) in the nontested group ( P < .001). Conclusions . Patients undergoing testing for strep pharyngitis were younger, had lower rates of appendicitis, and had a higher rate of negative appendectomy. A diagnosis of concurrent appendicitis and strep pharyngitis is rare. In cases of patients with sufficient symptoms to warrant testing for strep pharyngitis a diagnosis of appendicitis is less likely and surgical intervention leads to higher negative appendectomy rates.